OSTENTATIOUSLY EMOTIVE_LOADED LANGUAGE BY BBC IN THE COVERAGE OF TŪFĀN AL-AQSA - Mohammad Ahmad Thawabteh (Studii de gramatică contrastivă)
An attack on Israeli Occupation Forces (IOF) on October 7th, 2023 drastically changed the 24-hour news cycle. Palestinian militant groups orchestrated a blitzkrieg on IOF headquarters in the Gaza Strip borders in such an organized military precision, earning an appellation Tūfān al-Aqsa (literally, ‘Al-Aqsa Flood’). To soothe its fury, IOF declared an all-out war on Gaza targeting resistance groups, and immediately embarked on a military operation against Hamas’s authority and its ability to wage any military actions against IOF in future. Concomitant with the war has been an increasingly bitter war of words by many pro-Israel media outlets world-wide. The present paper examines the media coverage of the war in the aftermath of the assault as can be illustrated in the finely-employed emotive-loaded language by the BBC. The paper reveals that the language has been rich in emotive overtones and clearly pictured that the IOF as being victimized by the groups’ brutality, and envisaged the groups as cowardly thugs which should be liquidated with no mercy. The paper shows that the power of the language aims to deflect international condemnation of the military operation inflicting heavy casualties on innocent Gazans and attempts to show full solidarity with Israel.